Takbiran Keliling dalam Pandangan Max Weber sebagai Teori Tindakan - Riswandi Sobana Kusuma (Gunung Djati Conference Series, 2023)
This study aims to discuss takbir around in Max Weber's view as a theory of action. This research uses a qualitative approach by applying a literature study. The material object of this research is the takbir around, while the formal object is Max Weber's views on the theory of action. The results and discussion show that takbir around the community can be understood as social action and also community culture. This study concludes that takbir around in Max Weber's theory of action can be classified as a value-oriented rational act, in which this action is directed at societal, Islamic, and Indonesian values.